Involvement of FAK-ERK2 signaling pathway in CKAP2-induced proliferation and motility in cervical carcinoma cell lines - Qi-sang Guo (Nature Portfolio, 2017)
Abstract Cervical carcinoma is the fourth most common cause of death in woman, caused by human papillomavirus (HPV) infections and arising from the cervix. Cytoskeleton-associated protein 2 (CKAP2), also known as tumor-associated microtubule-associated protein, has been linked to tumorigenic effects. In the present study, we screened CKAP2 as a new candidate gene which promotes development of cervical carcinoma, in two independent datasets (TCGA and GSE27678). Results showed that CKAP2 expression was significantly up-regulated in cervical cancerous tissues compared with normal counterparts. Gene set enrichment analysis (GSEA) showed that metastasis, cell cycle and FAK pathways were related with elevated CKAP2 expression. Knockdown of CKAP2 expression significantly inhibited cell proliferation, migration and invasion both in HeLa and C-33A cells. And depletion of CKAP2 down-regulated the expression of metastasis and cell cycle related proteins as well as the phosphorylation of ERK2 (p-ERK2), except E-cadherin. In vivo experiment revealed that knockdown of CKAP2 inhibited C-33A cells proliferation. However, FAK inhibitor PF-562271 and ERK2 inhibitor VX-11e treatment significantly inhibited CKAP2 overexpression-induced cell proliferation, migration and invasion in SiHa cells. In conclusion, our study suggests that CKAP2 acts as a functional oncogene in cervical carcinoma development and may exert its function by targeting FAK-ERK2 signaling pathway.